2010
DOI: 10.1016/j.jhealeco.2009.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Do red herrings swim in circles? Controlling for the endogeneity of time to death

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 15 publications
1
44
0
2
Order By: Relevance
“…The inclusion of TTD in models has led to strong debates about endogeneity (Felder et al, 2009). Felder et al (2009 have shown that while endogeneity is present, it is a small issue: TTD influences costs more than vice versa.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The inclusion of TTD in models has led to strong debates about endogeneity (Felder et al, 2009). Felder et al (2009 have shown that while endogeneity is present, it is a small issue: TTD influences costs more than vice versa.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…11 Concerning potential endogeneity of TTD, many previous studies have attempted to deal with it (e.g. Weaver et al, 2009;Felder et al, 2010;Stearns and Norton, 2004;Zweifel et al, 2004). The majority of studies, however, focused on the possibility of TTD being endogenous to acute or total HCE as the amount of care consumed is found to increase longevity (Hall and Jones, 2007;Becker et al, 2005).…”
Section: Endogeneitymentioning
confidence: 99%
“…None of these studies were able to appropriately solve the endogeneity of TTD because valid instruments were lacking. Studies that partly corrected for endogeneity bias concluded that the effect of TTD on the level of HCE is underestimated in the presence of endogeneity (Weaver et al, 2009;Stearns and Norton, 2004;Felder et al, 2010). In the specific case of LTCE, however, the endogeneity problem is probably more limited.…”
Section: Endogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Im Folgenden werden zwei dieser Kontroversen exemplarisch dargestellt. Eine Kontroverse setzt sich mit dem Einfluss des demografischen Wandels und des medizinisch-technischen Fortschritts auf die Gesundheitsausgaben auseinander [64,65,66,67]. In der Tendenz zeigen diese Arbeiten, trotz aller methodischen Unterschiede, dass der reine demografische Effekt auf die Gesundheitsausgaben überschätzt wird.…”
Section: Wissenschaftliche Kontroversenunclassified